Developing Android-Based Learning Media to Enhance Vocabulary Mastery of Primary School Students - Duwi Susanti; Chusna Apriyanti; Samsul Hadi (Intensive Journal, 2024)
The importance of exciting learning media cannot be ignored in education. This research aims to develop Android-based learning media to improve fourth-grade elementary school students’ vocabulary mastery. Besides, this also finds out the feasibility and effectiveness of the application. This learning media uses the ADDIE development model, which involves five stages: analysis, design, development, implementation, and evaluation. The research results show that the application developed, called the LEVO App, can significantly improve students’ vocabulary mastery. Trials were carried out at several stages, including one-on-one, small group, and field trials, with student response results. Apart from that, the results of the pre-test and post-test show a significant increase in students’ vocabulary mastery after using this learning media. Validation by media experts and material experts also indicates that this application is very suitable for use as a learning media. Thus, it is hoped that developing Android-based learning media can be an effective and efficient solution for improving elementary school students’ English language skills.Keywords: ADDIE Model, LEVOApp, Vocabulary, Teaching Vocabulary